Case report: Pregnancy and birth following the use of letrozole in ovulation induction - Noriega Portella, Luis (2015)
First pregnancy and live birth occurs in assisted fertility clinic in Lima, Peru then obtained from the use of letrozole to stimulate ovulation in a patient 35, with secondary infertility of three years of development and two daughters of 8 and 7 year old. The patient was stimulated letrozole 2.5 mg / day, orally, from third to seventh day of the cycle, associated with hMG, 75 IU / day, IM, from the seventh day in use in October 0000 IU micronized progesterone as luteal support . The case demonstrates the usefulness of letrozole to induce ovulation as an alternative to other ovulation-inducing agent.